Dried blood spot improves global access to aquaporin‐4‐IgG testing for neuromyelitis optica - Nisa Vorasoot; Yahya J. Abdulrahman; Farrah Mateen; James P. Fryer; Vyanka Redenbaugh; Jessica A. Sagen; Abdu K. Musubire; Sarah M. Jenkins; Amy P. Gorsh; John J. Chen; Anastasia Zekeridou; Andrew McKeon; et al. (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective This study aimed to evaluate the diagnostic accuracy of dried blood spot (DBS) compared with conventional serum Aquaporin‐4‐IgG (AQP4‐IgG) testing. Methods Prospective multicenter diagnostic study was conducted between April 2018 and October 2023 across medical centers in the United States, Uganda, and the Republic of Guinea. Neuromyelitis optica spectrum disorder (NMOSD) patients and controls collected blood on filter paper cards along with concurrent serum samples. These samples underwent analysis using flow cytometric live‐cell‐based assays (CBA) and enzyme‐linked immunosorbent assay (ELISA) to determine AQP4 serostatus. The accuracy of AQP4‐IgG detection between DBS and serum (gold standard) was compared. Results Among 150 participants (47 cases, 103 controls), there was a strong correlation between DBS and serum samples (Spearman's correlation coefficient of 0.82). The AUC was 0.97 (95% CI: 0.92–0.99). AQP4‐IgG detection through DBS showed 87.0% sensitivity (95% CI: 0.74–0.95) and 100% specificity (95% CI: 0.96–1.00) using CBA, and 65.2% sensitivity (95% CI: 0.43–0.84) and 95.2% specificity (95% CI: 0.76–0.99) using ELISA. Serum ELISA demonstrated 69.6% sensitivity (95% CI: 0.47–0.87) and 98.4% specificity (95% CI: 0.91–0.99). The stability of DBS in detecting AQP4‐IgG persisted over 24 months for most cases. Interpretation The DBS represents a viable alternative for detecting AQP4‐IgG in resource‐limited settings to diagnose NMOSD, offering high sensitivity and specificity comparable to serum testing. Moreover, DBS has low shipping costs, is easy to administer, and is suitable for point‐of‐care testing.